Optimalisasi Limbah Serbuk Gergaji Kayu Jati (Tectona grandis L.f) Sebagai Adsorben Logam Berat Kobalt (Co) dengan Metode Aktivasi Kimia: Optimization of Teak Wood Sawdust Waste (Tectona grandis L.f) as Heavy Metal Adsorbent of Cobalt (Co) by Chemical Activation Method - Faradin, Faradin; Muharti, Asti; Dinafa, Nazwa Jinanti; Widiyanto, Holisha (KOVALEN: Jurnal Riset Kimia, 2024)
Teak wood (Tectona grandis L.f.), a high-quality wood commonly used in Indonesia, specifically in the Cilegon area, has the potential to be used as an alternative to reduce environmental pollution. This research aimed to test teak wood sawdust waste as an adsorbent for cobalt heavy metal, create activated charcoal from the sawdust waste for the same purpose, and determine the optimal conditions for treatment with and without chemical activation. Industrial waste samples were found to contain 50.7 ppm of cobalt metal through ICPS testing. Activated chemical adsorption, without activation and with industrial wastewater mixture, resulted in a decrease in cobalt metal concentration by 78.2% or 11.08 ppm. The optimal conditions for activated chemical adsorption were found at a pH of 5, an adsorbent mass of 600 mg, and a time of 40 minutes, resulting in decreases of 60.9% (21.2751 ppm), 71% (15.7821 ppm) and 67.7% (17.5812 ppm), respectively. The results show that teak wood sawdust waste can effectively adsorb cobalt heavy metal, providing a potential solution for industrial wastewater treatment.